First results of a new quadrupole minimum-B permanent magnet electron cyclotron resonance ion source. (1st December 2022) - Kalvas, T; Toivanen, V; Kosonen, S T; Koivisto, H; Tarvainen, O; Maunoury, L
Abstract: The first experimental results of a novel permanent magnet electron cyclotron resonance ion source (ECRIS) with a minimum-B quadrupole magnetic field topology are presented. Bremsstrahlung measurements indicate that the electrons can reach energies of 150–200 keV. Ion charge states up to Ar 11+ and Kr 15+ were detected in the charge state distributions of the extracted beams. Measurements in pulsed operation mode reveal an afterglow peak, which implies that high charge state ions are confined electrostatically similar to a conventional ECRIS. The potential applications and future development of the ion source are discussed.